A small-scale study on dancing for people living with Parkinson’s disease - Ann Björkdahl; Sofi Fristedt; Katarzyna Filipowicz; Paula Bergman; Ida-Klara Johansson; Iolanda Santos Tavares Silva (PLoS ONE, 2025)
Background People with Parkinson’s disease (PD) need life-long rehabilitative interventions to slow disease progression and reduce impact of the disease on daily life activities. To be sustainable for the individual, activities should have a positive impact on physical, cognitive and mental health, and should be appealing and meaningful. Aim To quantitatively evaluate the health-related effects of a 10-week dance program for patients with PD. Methods A cross-over design with two groups. Group 1 undertook 10 weeks of dance classes; after that, group 2 began their 10 weeks of dance classes. Assessments of both groups at four timepoints (baseline, 10, 20 and 30 weeks) included physical tests and self-reported questionnaires to assess cognition, self-efficacy, well-being, fatigue, and health-related quality of life. The analysis involved comparisons of results after the dance and non-dance periods, for all instruments. Results The analyses could not show any significant differences between the assessments after the dance period compared to after the no dance period. Conclusion Despite the lack of quantitative evidence of the positive experiences earlier described from focus groups, the study provided insights into how future research could be organised to better capture the multifaceted benefits. Furthermore, the study provides additional evidence that dance as a health-promoting activity in Parkinson’s disease should be viewed in a longer-term perspective.